Prevalence and Risk Factors of Drug-induced Gingival Overgrowth in Hypertensive Patients - Taib, Haslina; Mohd Radzwan, Muhammad Haziq; Sabaruddin, Muhammad Annurdin; Wan Mohamad, Wan Majdiah; Mohamad, Noraini (Journal of Dentistry Indonesia, 2021)
Gingival overgrowth (GO) or enlargement is an unwanted effect occurring on the gingiva that commonly associated with medications. Hypertension is a global burden systemic conditions and showed high prevalent and more patients are taking antihypertensive drugs. Objective: This study aimed to assess the prevalence of drug-induced gingival overgrowth (DIGO) and its associated risk factors among hypertensive patients attending Hospital Universiti Sains Malaysia, Kelantan, Malaysia. Methods: A total of 42 patients with the mean age of 57.1 (SD=9.3) years had participated in this cross-sectional study. They were recruited if they had consumed anti-hypertensive agents for at least 6 months. Demographic data and oral hygiene status were recorded and the presence of DIGO was assessed based on clinical index for gingival overgrowth. Data were analyzed using SPSS version 24.0 with p < 0.05 is considered statistically significant. Results: Majority of patients were taking calcium channel blockers (CCB) (81.0%) with amlodipine reported as the most common antihypertensive prescribed (47.6%). About 52% presented with DIGO and among them 55.9% were in those on CCB by which 9.5% presented with clinically significant enlargement. Except for gingivitis, oral hygiene status and demographic data were not significant risk factors for DIGO (p > 0.05). Conclusion: We found that DIGO is prevalent among hypertensive patients on CCB and its occurrence is coexists with gingivitis. Therefore, periodontal assessment is recommended among these patients for early detection and management of drug-induced gingival overgrowth.